PERAN GURU MATA PELAJARAN AKIDAH AKHLAK DALAM MENANAMKAN NILAI-NILAI AKHLAK TERPUJI PADA SISWA KELAS VIII MTS AL-FATAH BANJARNEGARA - Fitriani Nur Amalia; Asep Sunarko; Nasokah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to; 1.) To understand the concept of teachers in the subject of moral beliefs and instilling commendable moral values; 2) To find out the role of the moral aqidah subject teacher in instilling moral values ​​in class VIII students at Mts Al Fatah Banjarnegara; 3) To determine the supporting and inhibiting factors in the role of moral aqidah subject teachers in instilling commendable moral values ​​in students of class VIII Mts Al Fatah Banjarnegara. This research uses a qualitative approach with field research and uses descriptive methods. The subjects of the study consisted of Akidah Akhlak subject teachers, grade VIII students totaling 145 children, and administrators of Islamic boarding schools. Data collection techniques in this study were observation, interviews, and documentation. While the data analysis techniques used range from 1) Data reduction; 2) Data presentation; and 3) Drawing conclusions/verification.